Oncogenic KPNA2 Serves as a Biomarker and Immune Infiltration in Patients With HPV Positive Tongue Squamous Cell Carcinoma - Gao, Li; Li, Ying; Yu, Cheng; Liu, Dong-Xu; Wu, Ke-Han; Wei, Zhi-Li; Liu, Ming-Yue; Yu, Lei (Frontiers in Oncology, 2022)
Human tongue squamous cell carcinoma (TSCC), the most prevalent type of oral cancer, is associated with human papillomavirus (HPV) infection. Our previous work showed Karyopherin α2 (KPNA2), as an oncogene of TSCC, by relegating the p53/ autophagy signaling pathway. Nevertheless, the significance of KPNA2 in TSCC pathogenesis has not been established. KPNA2 levels were evaluated via the TCGA database, and its effects on survival outcomes were assessed by LASSO, Kaplan‐Meier, and COX regression analyses. CIBERSORT and ESTIMATE investigated the relationships between KPNA2 and immune infiltration. At the same time, KPNA2 and HPV injection was analyzed by immunohistochemistry. In addition, the association between downstream molecular regulation pathways and KPNA2 levels was determined by GO, GSEA, and WGCNA. In TSCC, KPNA2 levels were associated with clinical prognosis and tumor grade. Moreover, KPNA2 may be involved in cancer cell differentiation and facilitates tumor-related genes and signaling pathways, such as Cell Cycle, Mitotic G1 phase, G1/S transition, DNA Repair, and Transcriptional Regulation TP53 signaling pathways. Nevertheless, regulatory B cells, follicular helper B cells, and immune and stromal scores between low- and high-KPNA2 expression groups were insignificant. These results imply that KPNA2 is highly involved in tumor grade and prognosis of TSCC. KPNA2 levels correct with HPV 16 markedly regulated cell differentiation, several oncogenes, and cancer‐related pathways.